If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 7(x + -14) = 5(x + -14) Reorder the terms: 5x + 7(-14 + x) = 5(x + -14) 5x + (-14 * 7 + x * 7) = 5(x + -14) 5x + (-98 + 7x) = 5(x + -14) Reorder the terms: -98 + 5x + 7x = 5(x + -14) Combine like terms: 5x + 7x = 12x -98 + 12x = 5(x + -14) Reorder the terms: -98 + 12x = 5(-14 + x) -98 + 12x = (-14 * 5 + x * 5) -98 + 12x = (-70 + 5x) Solving -98 + 12x = -70 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -98 + 12x + -5x = -70 + 5x + -5x Combine like terms: 12x + -5x = 7x -98 + 7x = -70 + 5x + -5x Combine like terms: 5x + -5x = 0 -98 + 7x = -70 + 0 -98 + 7x = -70 Add '98' to each side of the equation. -98 + 98 + 7x = -70 + 98 Combine like terms: -98 + 98 = 0 0 + 7x = -70 + 98 7x = -70 + 98 Combine like terms: -70 + 98 = 28 7x = 28 Divide each side by '7'. x = 4 Simplifying x = 4
| 10(2n-3)=(10n+6)+4 | | y=3x^2-4x-6 | | 36-25x^2=0 | | y=x^2-6 | | 3x+12=7*3 | | 4x+(x-9)=4(x-10) | | 6(3n-5)=(9n+8)+5 | | ax+2=aw | | 4=t-5s | | 5n-8=-48 | | (x^3+4x^2)-(2x-8)=0 | | 3n-9=-27 | | 3-6(4+8n)=-21+10n | | 20r^2-41r+20=0 | | x(10x+24)=0 | | (s+16)(s+81)=0 | | 7-3x=15+5x | | 3-6(4+8n)=21+10n | | c(c+3)=0 | | y-(2y-5)=94 | | (3s+7)(s+6)=0 | | (3)-(-4)= | | s^2+11s+24=0 | | c^2-11c+18=0 | | 4x-7=3.5 | | -4(t+2)=12 | | s^7-7s=0 | | 32-14=3(x-4) | | -29+7x=-5(1-2x) | | 12x=6x+24 | | 12x=5x+24 | | 8y+2-6y=3+t-10 |